Analysis of dispersal characteristics of five food powders for avoiding unintentional food allergen cross-contact during food processing - Hiroyuki Hashimoto; Koichiro Ogata; Tatsuya M. Ikeda; Masato Yoshimitsu; Kyohei Kiyota (Journal of Food Engineering, 2026)

Pollen-pistil interaction and asymmetric reproductive interference in Veronica species - Sachiko Nishida; Naoko Watanabe; Keisuke Hashimoto; Yuyan Zhang; Ko-Ichi Takakura; Masahiro M. Kanaoka (Journal of Plant Research, 2026)

Recent advancements in aquaculture genetics - José M. Yáñez; Roberto Neira; Diogo T. Hashimoto; Delphine Lallias; Peng Xu; Dean R. Jerry (Aquaculture, 2025)

Generation of canine gallbladder cholangiocyte organoids from healthy and gallbladder mucocele patient dogs for functional analysis of anion channels - Itsuma Nagao; Hirotaka Tomiyasu; Yuko Goto-Koshino; Kota Nakase; Takumi Tsuruta; Yuto Namiki; Ryuichiro Sato; Yu Takahashi; Yuko Hashimoto; Yosuke Takahashi; Naohiro Takahashi; James K. Chambers; et al. (The Veterinary Journal, 2025)

Spatiotemporal dynamics of bioproduction systems and ecosystem services in the Baroro and Pagsanjan-Lumban watersheds, Philippines - Nico R. Almarines; Shizuka Hashimoto; Juan M. Pulhin; Canesio D. Predo.; Florencia B. Pulhin; Angelica T. Magpantay; Osamu Saito (Paddy and Water Environment, 2025)

Management strategies for shrinking and aging tree plantations are constrained by the synergies and trade-offs between carbon sequestration and other forest ecosystem services - Jumpei Toriyama; Shoji Hashimoto; Katsuhiro Nakao; Taku M. Saitoh; Tomohiro Nishizono; Kentaro Uchiyama; Masatake G. Araki; Wataru Murakami; Yasumasa Hirata (Journal of Environmental Management, 2025)

Genomic predictions for resistance to Aeromonas hydrophila in pacu (Piaractus mesopotamicus) - Shisley C.S. Manso; Baltasar F. Garcia; Vito A. Mastrochirico-Filho; Fábio Porto-Foresti; José M. Yáñez; Diogo T. Hashimoto (Aquaculture, 2024)

Genetic parameters for host-response to acanthocephaliasis caused by the endoparasite Neoechinorhynchus buttnerae in the Amazon fish Colossoma macropomum - John F.G. Agudelo; Baltasar F.G. Neto; Vito A. Mastrochirico-Filho; Raquel B. Ariede; Luis F.S. Moreira; Leilane da Silva Noronha; José M. Yáñez; Alexandre Honczaryk; Gustavo M.R. Valladão; Diogo T. Hashimoto (Aquaculture, 2024)

A watershed-scale evapotranspiration model considering forest type, stand parameters, and climate factors - Shodai Inokoshi; Takashi Gomi; Chen-Wei Chiu; Yuichi Onda; Asahi Hashimoto; Yupan Zhang; Taku M. Saitoh (Forest Ecology and Management, 2023)

Towards a better future for biodiversity and people: Modelling Nature Futures - HyeJin Kim; Garry D. Peterson; William W.L. Cheung; Simon Ferrier; Rob Alkemade; Almut Arneth; Jan J. Kuiper; Sana Okayasu; Laura Pereira; Lilibeth A. Acosta; Rebecca Chaplin-Kramer; Eefje den Belder; et al. (Global Environmental Change, 2023)

Bringing the Nature Futures Framework to life: creating a set of illustrative narratives of nature futures - América Paz Durán; Jan J. Kuiper; Ana Paula Dutra Aguiar; William W. L. Cheung; Mariteuw Chimère Diaw; Ghassen Halouani; Shizuka Hashimoto; Maria A. Gasalla; Garry D. Peterson; Machteld A. Schoolenberg; Rovshan Abbasov; Lilibeth A. Acosta; et al. (Sustainability Science, 2023)
To halt further destruction of the biosphere, most people and societies around the globe need to transform their relationships with nature. The internationally agreed vision under the Convention of Biological Diversity—Living in harmony with nature—is that “By 2050, biodiversity is valued, conserved, restored and wisely used, maintaining ecosystem services, sustaining a healthy planet and delivering benefits essential for all people”. In this context, there are a variety of debates between alternative perspectives on how to achieve this vision. Yet, scenarios and models that are able to explore these debates in the context of “living in harmony with nature” have not been widely developed. To address this gap, the Nature Futures Framework has been developed to catalyse the development of new scenarios and models that embrace a plurality of perspectives on desirable futures for nature and people. In this paper, members of the IPBES task force on scenarios and models provide an example of how the Nature Futures Framework can be implemented for the development of illustrative narratives representing a diversity of desirable nature futures: information that can be used to assess and develop scenarios and models whilst acknowledging the underpinning value perspectives on nature. Here, the term illustrative reflects the multiple ways in which desired nature futures can be captured by these narratives. In addition, to explore the interdependence between narratives, and therefore their potential to be translated into scenarios and models, the six narratives developed here were assessed around three areas of the transformative change debate, specifically, (1) land sparing vs. land sharing, (2) Half Earth vs. Whole Earth conservation, and (3) green growth vs. post-growth economic development. The paper concludes with an assessment of how the Nature Futures Framework could be used to assist in developing and articulating transformative pathways towards desirable nature futures.

High-throughput phenotyping by deep learning to include body shape in the breeding program of pacu (Piaractus mesopotamicus) - Milena V. Freitas; Celma G. Lemos; Raquel B. Ariede; John F.G. Agudelo; Rubens R.O. Neto; Carolina H.S. Borges; Vito A. Mastrochirico-Filho; Fábio Porto-Foresti; Rogério L. Iope; Fabrício M. Batista; José R.F. Brega; Diogo T. Hashimoto (Aquaculture, 2023)

Genome-wide association study of host resistance to the ectoparasite Ichthyophthirius multifiliis in the Amazon fish Colossoma macropomum - Lieschen V. G. Lira; Vito A. Mastrochirico-Filho; Natalia J. Mendes; Raquel B. Ariede; José M. Yáñez; Diogo T. Hashimoto (Molecular Biology Reports, 2023)

The future of artificial intelligence in the context of industrial ecology - Franco Donati; Sébastien M. R. Dente; Chen Li; Xaysackda Vilaysouk; Andreas Froemelt; Rohit Nishant; Gang Liu; Arnold Tukker; Seiji Hashimoto (Journal of Industrial Ecology, 2022)
Artificial intelligence (AI) applications and digital technologies (DTs) are increasingly present in the daily lives of citizens, in cities and in industries. These developments generate large amounts of data and enhance analytical capabilities that could benefit the industrial ecology (IE) community and sustainability research in general. With this communication, we would like to address some of the opportunities, challenges, and next steps that could be undertaken by the industrial ecology community in this realm. This article is an adapted summary of the discussion held by experts in industrial ecology, AI, and sustainability during the 2021 Industrial Ecology Day conference session titled “The Future of Artificial Intelligence in the Context of Industrial Ecology.” In brief, building on previous studies and communications, we advise the industrial ecology community to: (1) create internal committees and working groups to monitor and coordinate AI applications within and outside the community; (2) promote and ensure transdisciplinary efforts; (3) determine optimal infrastructure and governance of AI for IE to minimize undesired effects; and (4) act on effective representation and on reduction of digital divides.

Undergraduate Curriculum Designed to Facilitate a Cancer Exercise Rehabilitation Program - Paulette M. Yamada; Cheri Teranishi-Hashimoto; Ariimana Temanaha (Journal of Cancer Education, 2022)

Actions to halt biodiversity loss generally benefit the climate - Yunne‐Jai Shin; Guy F. Midgley; Emma R. M. Archer; Almut Arneth; David K. A. Barnes; Lena Chan; Shizuka Hashimoto; Ove Hoegh‐Guldberg; Gregory Insarov; Paul Leadley; Lisa A. Levin; Hien T. Ngo; et al. (Global Change Biology, 2022)
The two most urgent and interlinked environmental challenges humanity faces are climate change and biodiversity loss. We are entering a pivotal decade for both the international biodiversity and climate change agendas with the sharpening of ambitious strategies and targets by the Convention on Biological Diversity and the United Nations Framework Convention on Climate Change. Within their respective Conventions, the biodiversity and climate interlinked challenges have largely been addressed separately. There is evidence that conservation actions that halt, slow or reverse biodiversity loss can simultaneously slow anthropogenic mediated climate change significantly. This review highlights conservation actions which have the largest potential for mitigation of climate change. We note that conservation actions have mainly synergistic benefits and few antagonistic trade‐offs with climate change mitigation. Specifically, we identify direct co‐benefits in 14 out of the 21 action targets of the draft post‐2020 global biodiversity framework of the Convention on Biological Diversity, notwithstanding the many indirect links that can also support both biodiversity conservation and climate change mitigation. These relationships are context and scale‐dependent; therefore, we showcase examples of local biodiversity conservation actions that can be incentivized, guided and prioritized by global objectives and targets. The close interlinkages between biodiversity, climate change mitigation, other nature's contributions to people and good quality of life are seldom as integrated as they should be in management and policy. This review aims to re‐emphasize the vital relationships between biodiversity conservation actions and climate change mitigation in a timely manner, in support to major Conferences of Parties that are about to negotiate strategic frameworks and international goals for the decades to come.

Comparisons among populations and individuals to evaluate pollen–pistil interaction as a mechanism of reproductive interference in Taraxacum - Keisuke Hashimoto; Akane Yamamoto; Masahiro M. Kanaoka; Akiyo Naiki; Ko-Ichi Takakura; Sachiko Nishida (Journal of Plant Research, 2022)

Total environmental impacts of Japanese material production - Chika Aoki‐Suzuki; Sébastien M. R. Dente; Daisuke Tanaka; Chihiro Kayo; Shinsuke Murakami; Chiharu Fujii; Kiyotaka Tahara; Seiji Hashimoto (Journal of Industrial Ecology, 2021)
Decoupling well‐being from resource use and its associated environmental impacts through resource efficiency and circular economy has become the mainstream agenda for sustainable development. Resource productivity and material flow indicators have been widely used to evaluate resource decoupling. Several approaches have been introduced in Europe to calculate the life cycle environmental impact of resource use at the macro‐level and assess impact decoupling. However, no studies have been conducted to estimate the overall aggregated environmental impact (total environmental impact) associated with resource use in all resource categories using statistical data at the national level and life cycle inventory databases in Japan. This study is the first assessment of the total environmental impact at the national level in Japan, particularly addressing the production process for 213 materials. The study makes it possible to distinguish the 4 phases for environmental impact generation (foreign supply chain, domestic supply chain, production process, and use), 12 environmental impact areas, and the resource category (biomass, fossil, metal, and non‐metallic mineral) of each material. The study shows that there is a higher impact generated by production and foreign supply chain phases in biomass and fossil resources such as crops, livestock, dairy products, and petroleum and coal products as well as some metals (steel and copper). These results imply that measures to reduce resource use and improve energy efficiency in direct production and foreign supply chains through local resource procurement and further resource‐efficient approaches, including the circular economy, should be prioritized for Japan, with its resource‐scarce and manufacturing‐oriented economy.

Diverse steroidogenic pathways in the marine alga Aurantiochytrium - Masaki Yoshida; Motohide Ioki; Hiroshi Matsuura; Akinori Hashimoto; Kunimitsu Kaya; Nobuyoshi Nakajima; Makoto M. Watanabe (Journal of Applied Phycology, 2020)

The role of dispersed ash in orbital-scale time-series studies of explosive arc volcanism: insights from IODP Hole U1437B, Northwest Pacific Ocean - Kate Corry-Saavedra; Julie C. Schindlbeck; Susanne M. Straub; Masafumi Murayama; Louise L. Bolge; Arturo Gómez-Tuena; Yoshitaka Hashimoto; Jon D. Woodhead (International Geology Review, 2019)

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Variation in the strength of reproductive interference from an alien congener to a native species in Taraxacum - Sachiko Nishida; Keisuke Hashimoto; Masahiro M. Kanaoka; Ko-Ichi Takakura; Takayoshi Nishida (Journal of Plant Research, 2017)

Tropical cyclone activity in nested regional and global grid-refined simulations - Atsushi Hashimoto; James M. Done; Laura D. Fowler; Cindy L. Bruyère (Climate Dynamics, 2016)

Origin of B chromosomes in the genus Astyanax (Characiformes, Characidae) and the limits of chromosome painting - Duílio M. Z. de A. Silva; Sandro Natal Daniel; Juan Pedro M. Camacho; Ricardo Utsunomia; Francisco J. Ruiz-Ruano; Manolo Penitente; José Carlos Pansonato-Alves; Diogo Teruo Hashimoto; Claudio Oliveira; Fábio Porto-Foresti; Fausto Foresti (Molecular Genetics and Genomics, 2016)

Relationships between capture-site characteristics and capture levels of the invasive mongoose on Amami-Oshima Island, Japan - H. Komine; K. Takeshita; S. Abe; T. Ishikawa; M. Kimura; T. Hashimoto; K. Kitaura; T. Morosawa; K. Seki; K. Kaji (Biological Invasions, 2016)

A new species of Trichodina Ehrenberg, 1830 (Ciliophora: Trichodinidae) from Rhamdia quelen (Siluriformes: Heptapteridae) and Gymnotus sp. (Teleostei: Gymnotidae) in Brazil - Gabriela S.O. Hashimoto; Natalia C. Marchiori; Santiago B. Pádua; Márcia M. Ishikawa; Juan R.E. Garcia; Maurício L. Martins (Acta Parasitologica, 2016)
The present study describes a new species of

Triassic–Jurassic granites on the Lord Howe Rise, northern Zealandia - N. Mortimer; R. E. Turnbull; J. M. Palin; A. J. Tulloch; N. Rollet; T. Hashimoto (Australian Journal of Earth Sciences, 2015)

Magnetically-modified natural biogenic iron oxides for organic xenobiotics removal - I. Safarik; J. Filip; K. Horska; M. Nowakova; J. Tucek; M. Safarikova; H. Hashimoto; J. Takada; R. Zboril (International Journal of Environmental Science and Technology, 2015)

Association between perceived inadequate staffing and musculoskeletal pain among hospital patient care workers - Seung-Sup Kim; Cassandra A. Okechukwu; Jack T. Dennerlein; Leslie I. Boden; Karen Hopcia; Dean M. Hashimoto; Glorian Sorensen (International Archives of Occupational and Environmental Health, 2014)

Identification of a gene for an ancient cytokine, interleukin 15-like, in mammals; interleukins 2 and 15 co-evolved with this third family member, all sharing binding motifs for IL-15Rα - Johannes M. Dijkstra; Fumio Takizawa; Uwe Fischer; Maik Friedrich; Veronica Soto-Lampe; Christophe Lefèvre; Matthias Lenk; Axel Karger; Taei Matsui; Keiichiro Hashimoto (Immunogenetics, 2014)

Chromosomal organization of repetitive DNA sequences in Astyanax bockmanni (Teleostei, Characiformes): dispersive location, association and co-localization in the genome - Duílio M. Z. A. Silva; José Carlos Pansonato-Alves; Ricardo Utsunomia; Sandro Natal Daniel; Diogo Teruo Hashimoto; Claudio Oliveira; Fabio Porto-Foresti; Fausto Foresti (Genetica, 2013)

A large hydrothermal reservoir beneath Taal Volcano (Philippines) revealed by magnetotelluric resistivity survey: 2D resistivity modeling - Y. Yamaya; P. K. B. Alanis; A. Takeuchi; J. M. Cordon; T. Mogi; T. Hashimoto; Y. Sasai; T. Nagao (Bulletin of Volcanology, 2013)

Effects of Pituitary Adenylate Cyclase Activating Polypeptide on Human Sperm Motility - R. Brubel; P. Kiss; A. Vincze; A. Varga; A. Varnagy; J. Bodis; L. Mark; E. Jambor; G. Maasz; H. Hashimoto; Zs. Helyes; G. Toth; et al. (Journal of Molecular Neuroscience, 2012)

‘Better off alone than in bad company’: agonistic colour display in mimetic juveniles of two ephippid species - B. Barros; Y. Sakai; H. Hashimoto; K. Gushima; M. Vallinoto (Journal of Fish Biology, 2012)
Comparative field observations of agonistic interactions in juvenile leaf‐mimicking Platax orbicularis and Chaetodipterus faber (Ephippidae) were conducted in coastal waters of the Pacific and Atlantic Oceans. Similar agonistic behaviour was observed in the two species, in which individuals stopped displaying their mimetic colouration during encounters with conspecifics, to display conspicuous colours, such as transverse stripes along the body. These events were observed occasionally, almost invariably in individuals of smaller body size. Larger‐bodied individuals of both species spent less time in agonistic displays. The absolute size of the fish, however, did not appear to affect the outcome of the encounter, suggesting that dominance is a temporary condition, based on the relative size of the opponents during encounters.

Schizymenia dubyi (Rhodophyta, Schizymeniaceae), a new introduced species in Argentina - ME Ramirez; JD Nuñez; EH Ocampo; CV Matula; M Suzuki; T Hashimoto; M Cledón (New Zealand Journal of Botany, 2012)
Schizymenia dubyi (Chauvin ex Duby) J. Agardh is a red alga of the order Nemastomatales that is native to Europe, Asia and Oceania. The first specimen of this seaweed from the Argentinian coast was collected in the Chapadmalal intertidal wave‐cut platform (38°12′S, 57°40′W) in September 2008. Taxonomic identification of the species was made on the basis of vegetative and reproductive characters and confirmed by DNA sequence analysis of the rbc L gene. The S. dubyi samples collected in the field were represented by foliose gametophytes as well as crustose tetrasporophytes. The gametophytes were distributed in patches of c. 50% coverage of the analysed quadrants ( n = 20). Gametophyte abundance was 3.1±2.5 (mean±SD) plants per quadrant (0.04 m 2 ). All these were fertile females. Molecular results placed the specimens from Argentina within the S. dubyi clade, closely related to S. dubyi from Japan and France.

Androgen Receptor Overexpression Is Neuroprotective in Experimental Stroke - Patricia Ayala; Masayoshi Uchida; Kozaburo Akiyoshi; Jian Cheng; Joel Hashimoto; Taiping Jia; Oline K. Ronnekleiv; Stephanie J. Murphy; Kristine M. Wiren; Patricia D. Hurn (Translational Stroke Research, 2011)

Removal of Cr(VI) from aqueous solutions by the culm of bamboo grass treated with concentrated sulfuric acid - M. Koroki; S. Saito; H. Hashimoto; T. Yamada; Masakazu Aoyama (Environmental Chemistry Letters, 2010)

Antifouling properties of tough gels against barnacles in a long-term marine environment experiment - T. Murosaki; T. Noguchi; K. Hashimoto; A. Kakugo; T. Kurokawa; J. Saito; Y. M. Chen; H. Furukawa; J. P. Gong (Biofouling, 2009)

Cell and receptor type-specific alterations in markers of GABA neurotransmission in the prefrontal cortex of subjects with schizophrenia - David A. Lewis; Takanori Hashimoto; Harvey M. Morris (Neurotoxicity Research, 2008)

Proliferation of kuchijirosho causative agent in a fugu‐derived cell line - E Hashimoto; T Miyadai; M Ohtani; S‐I Kitamura; M‐J Oh (Journal of Fish Diseases, 2008)
Kuchijirosho is a fatal disease of commercially cultured fugu, Takifugu rubripes . The transmissible nature of kuchijirosho strongly suggests that an infectious pathogen is the causative agent. Because it is filtrable, the agent is thought to be a virus; however, it has not yet been identified. The lack of a permissive cell line for the putative kuchijirosho‐causing agent (KCA) has hindered research on the identification of this pathogen. We inoculated brain extract prepared from kuchijirosho‐affected fugu onto an established fugu cell line, fugu eye, and observed that cytopathic effect appeared 7 days after inoculation. Injection of the culture medium of infected fugu eye cells into fugu resulted in the onset of kuchijirosho, indicating that fugu eye cells are able to proliferate KCA. An infectious fraction separated by sodium iottalamate density gradient centrifugation showed a density of 1.15 g mL −1 equivalent to that of KCA derived from affected fugu brain. To determine whether the genome of KCA is RNA or DNA based, nucleotide synthesis inhibitors were applied to inoculated fugu eye cell line to influence the production of KCA. 5‐Fluorouracil but not IUdR showed a concentration‐dependent inhibition of KCA yield. These results suggest that KCA is an RNA virus.

Nucleotide sequence analysis of seven Japanese isolates of Plantago asiatica mosaic virus (PlAMV): a unique potexvirus with significantly high genomic and biological variability within the species - K. Komatsu; Y. Yamaji; J. Ozeki; M. Hashimoto; S. Kagiwada; S. Takahashi; S. Namba (Archives of Virology, 2008)

Complete nucleotide sequence of asparagus virus 3 - M. Hashimoto; J. Ozeki; K. Komatsu; H. Senshu; S. Kagiwada; T. Mori; Y. Yamaji; S. Namba (Archives of Virology, 2008)

Testicular toxicity of profenofos in matured male rats - Gihan Gamal Moustafa; Zein Shaban Ibrahim; Yoshiharu Hashimoto; Alkelch M. Alkelch; Kentaro Q. Sakamoto; Mayumi Ishizuka; Shoichi Fujita (Archives of Toxicology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Genome sequence of a Japanese isolate of Radish mosaic virus: the first complete nucleotide sequence of a crucifer-infecting comovirus - K. Komatsu; M. Hashimoto; K. Maejima; J. Ozeki; S. Kagiwada; S. Takahashi; Y. Yamaji; S. Namba (Archives of Virology, 2007)

Clathrin is involved in organization of mitotic spindle and phragmoplast as well as in endocytosis in tobacco cell cultures - H. Tahara; E. Yokota; H. Igarashi; H. Orii; M. Yao; S. Sonobe; T. Hashimoto; P. J. Hussey; T. Shimmen (Protoplasma, 2007)

Evaluation of benthic nutrient fluxes and their importance in the pelagic nutrient cycles in Suo Nada, Japan - M Jahangir SARKER; Tamiji YAMAMOTO; Toshiya HASHIMOTO; Takaya OHMURA (Fisheries Science, 2005)

Involvement of Aquaporin-5 Water Channel in Osmoregulation in Parotid Secretory Granules - M. Matsuki; S. Hashimoto; M. Shimono; M. Murakami; J. Fujita-Yoshigaki; S. Furuyama; H. Sugiya (The Journal of Membrane Biology, 2005)

Horizontal and Vertical Distribution of Estrogenic Activities in Sediments and Waters from Tokyo Bay, Japan - S. Hashimoto; A. Horiuchi; T. Yoshimoto; M. Nakao; H. Omura; Y. Kato; H. Tanaka; K. Kannan; J. P. Giesy (Archives of Environmental Contamination and Toxicology, 2005)

Genetic diversity and phylogeny of Japanese sake-brewing rice as revealed by AFLP and nuclear and chloroplast SSR markers - Z. Hashimoto; N. Mori; M. Kawamura; T. Ishii; S. Yoshida; M. Ikegami; S. Takumi; C. Nakamura (Theoretical and Applied Genetics, 2004)

Current Levels of Dioxins in Surface Soils from Santiago, Chile - Y. Takazawa; R. Verdugo; P. Richter; K. Kitamura; J.-W. Choi; S. Hashimoto; H. Ito; Y. Shibata; M. Morita (Bulletin of Environmental Contamination and Toxicology, 2004)

Comparative Analysis of the Ribosomal Componentsof the Hydrogenosome-Containing Protist, Trichomonas vaginalis - Nobuko Arisue; Yasushi Maki; Hideji Yoshida; Akira Wada; LidyaB. Snchez; Mikls Mller; Tetsuo Hashimoto (Journal of Molecular Evolution, 2004)

Development of PCR-based SNP markers for rice blast resistance genes at the Piz locus - K. Hayashi; N. Hashimoto; M. Daigen; I. Ashikawa (Theoretical and Applied Genetics, 2004)

Phylogenetic relationships of deep-sea mussels of the genus Bathymodiolus (Bivalvia: Mytilidae) - J.-I. Miyazaki; M. Shintaku; A. Kyuno; Y. Fujiwara; J. Hashimoto; H. Iwasaki (Marine Biology, 2004)

In situ pressure–temperature conditions of a tectonic mélange: Constraints from fluid inclusion analysis of syn‐mélange veins - Y. Hashimoto; M. Enjoji; A. Sakaguchi; G. Kimura (Island Arc, 2003)
Pressure and temperature (P–T) conditions of mélange formation are estimated from fluid inclusions within “syn‐mélange” veins developed in the necks of boudins of sandstone blocks in the mélange of the Shimanto accretionary complex, south‐west Japan. The mélange records décollement‐zone processes. P–T conditions are in the range of 81 (+15) to 235 (±18) MPa and 150 (±25) to 220 (±31)°C. Assuming a constant fluid‐pressure to lithostatic‐pressure ratio for each data set, we estimate a P–T gradient of between 10.0°C/km (+0.2/−1.5) (lithostatic pressure) and 4.2°C/km (+0.1/−0.9) (hydrostatic pressure) from these results. The estimated lithostatic P–T gradient is much lower than that calculated from the age of the subducting oceanic plate. The estimated P–T conditions suggest that the mélange was formed within the seismogenic zone (hypothesized from thermal modeling), although the deformation mechanism of mélange (i.e. dominant diffusive mass transfer mainly in shale matrix with minor brittle breakage mainly in sandstone blocks) does not show evidence of seismic deformation. In addition, at the time of syn‐mélange vein formation, a shale matrix of mélange has injected into the vein, which indicates a ductile deformation of shale. A possible explanation for this discrepancy is that the mélange was formed during the interseismic period.

Genetic similarity of outbreak populations of crown-of-thorns starfish (Acanthaster planci) that were 15years apart in Okinawa, Japan - M. Katoh; K. Hashimoto (Coral Reefs, 2003)

Peripheral nerve regeneration through alginate gel: analysis of early outgrowth and late increase in diameter of regenerating axons - T. Hashimoto; Y. Suzuki; M. Kitada; K. Kataoka; S. Wu; K. Suzuki; K. Endo; Y. Nishimura; C. Ide (Experimental Brain Research, 2002)

Simulation of the Transition of Earthquake Rupture from Quasi-static Growth to Dynamic Propagation - E. Fukuyama; C. Hashimoto; M. Matsu'ura (Pure and Applied Geophysics, 2002)

3-D Simulation of Earthquake Generation Cycles and Evolution of Fault Constitutitve Properties - C. Hashimoto; M. Matsu'ura (Pure and Applied Geophysics, 2002)

Retrolyc1 subfamilies defined by different U3 LTR regulatory regions in the Lycopersicon genus - P. Araujo; J. Casacuberta; A. Costa; R. Hashimoto; M.-A. Grandbastien; M.-A. Van Sluys (Molecular Genetics and Genomics, 2001)

Hemagglutinin genotype profiles of canine distemper virus from domestic dogs in Japan - M. Hashimoto; Y. Une; M. Mochizuki (Archives of Virology, 2001)

Structure of the infected cell protein 0 gene of canine herpesvirus - M. Miyoshi; M. Takiguchi; J. Yasuda; A. Hashimoto; A. Takada; K. Okazaki; H. Kida (Archives of Virology, 2000)

Antibacterial characteristics of magnesium oxide powder - J. Sawai; H. Kojima; H. Igarashi; A. Hashimoto; S. Shoji; T. Sawaki; A. Hakoda; E. Kawada; T. Kokugan; M. Shimizu (World Journal of Microbiology and Biotechnology, 2000)

Genetic contribution of the BAT2 gene microsatellite polymorphism to the age-at-onset of insulin-dependent diabetes mellitus - M. Hashimoto; N. Nakamura; H. Obayashi; F. Kimura; A. Moriwaki; G. Hasegawa; H. Shigeta; Y. Kitagawa; K. Nakano; M. Kondo; M. Ohta; M. Nishimura (Human Genetics, 1999)

Genetic contribution of the BAT2 gene microsatellite polymorphism to the age-at-onset of insulin-dependent diabetes mellitus - M. Hashimoto; N. Nakamura; H. Obayashi; F. Kimura; A. Moriwaki; G. Hasegawa; H. Shigeta; Y. Kitagawa; K. Nakano; M. Kondo; M. Ohta; M. Nishimura (Human Genetics, 1999)

Glycogen storage disease III subtypes and muscle weakness during childhood - M. Okubo; A. Horinishi; M. Hashimoto; H. Kanno; T. Murase (Human Genetics, 1999)

Structure of the immediate early gene of canine herpesvirus - M. Miyoshi; M. Takiguchi; J. Yasuda; A. Hashimoto; A. Takada; K. Okazaki; H. Kida (Archives of Virology, 1999)

Urine-associated horizontal transmission of Seoul virus among rats - H. Kariwa; M. Fujiki; K. Yoshimatsu; J. Arikawa; I. Takashima; N. Hashimoto (Archives of Virology, 1998)

A novel point mutation in an acceptor splice site of intron 32 (IVS32 A -12 →G) but no exon 3 mutations in the glycogen debranching enzyme gene in a homozygous patient with glycogen storage disease type IIIb - M. Okubo; Asako Horinishi; Norimasa Nakamura; Yoshiko Aoyama; Masaji Hashimoto; Yuzo Endo; Toshio Murase (Human Genetics, 1998)

Urine-associated horizontal transmission of Seoul virus among rats - H. Kariwa; M. Fujiki; K. Yoshimatsu; J. Arikawa; I. Takashima; N. Hashimoto (Archives of Virology, 1998)

Molecular systematics of vestimentiferan tubeworms from hydrothermal vents and cold-water seeps - M. B. Black; K. M. Halanych; P. A. Y. Maas; W. R. Hoeh; J. Hashimoto; D. Desbruyères; R. A. Lutz; R. C. Vrijenhoek (Marine Biology, 1997)

Production and recovery of an enzyme fromPseudomonas vesicularis var.povalolyticus PH that degrades polyvinyl alcohol - Y. Kawagoshi; Y. Mitihiro; M. Fujita; S. Hashimoto (World Journal of Microbiology and Biotechnology, 1997)

Effects of carp serum on the growth of goldfish fin cells in early passage - H. Hashimoto; H. Toyohara; Y. Yokoyama; M. Sakaguchi; K. Ozato; Y. Wakamatsu (Journal of Fish Biology, 1997)
The culture medium supplemented with carp serum and fetal bovine serum (FBS) promoted cell growth significantly and induced morphological change of goldfish fin cells in early passage as compared to the medium containing FBS alone. However, these effects were not observed in RBCF‐1, a cell line established from the goldfish fin. The sensitivity of the cells in early passage to carp serum suggests the following possibilities: (1) cells in early passage retain the ability to respond to growth‐promoting factors specifically included in carp serum; and (2) this ability is lost during the process of long‐term culture and/or long‐term culture in FBS eliminates cell groups showing high dependency of cell growth on carp serum.

Modes of Seoul virus infections: persistency in newborn rats and transiency in adult rats - H. Kariwa; M. Kimura; S. Yoshizumi; J. Arikawa; K. Yoshimatsu; I. Takashima; N. Hashimoto (Archives of Virology, 1996)

Heat shock induces HIV-1 replication in chronically infected promyelocyte cell line OM10.1 - K. Hashimoto; M. Baba; K. Gohnai; M. Sato; S. Shigeta (Archives of Virology, 1996)

Identification of mutation sites of a temperature-sensitive mutant of HCMV DNA polymerase activity - S. Ihara; M. Takekoshi; N. Mori; S. Sakuma; J. Hashimoto; Y. Watanabe (Archives of Virology, 1994)

Development of a psoriasis-like syndrome following lithium therapy - K. Hanada; M. Tasaki; I. Hashimoto; M. Sone; T. Yamaguchi (Biological Trace Element Research, 1987)

Enhanced production of interferon by ultraviolet irradiation and pretreatment with interferon in human diploid cells stimulated with polyinosinate-polycytidilate - H. Komatsu; N. Maehara; K. Shimoda; H. Hashimoto; T. Mori; T. Lee; S. Makino; M. Matumoto (Archives of Virology, 1982)